Peningkatan Kesadaran Pengelolaan Sampah Berbasis 3R Dan Pemberdayaan Masyarakat Melalui Program KKN Di Desa Srimukti, Tambun Utara - Sinaga, Zulkani; Aryan, Fajar Dwi; Fauzan, Gufron; Ismail, Muhamad Ikhtiar Raihan; Nugraha, Naufal; Aveline, Malita; Saputra, Dias Cahya; Mefia, Dinda; Putra, Hanifsa; Pradana, Satria Wahyu (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
KKN Group 9 from Bhayangkara University Jakarta Raya carried out its program in Srimukti Village, Tambun Utara Subdistrict, Bekasi Regency, an area with development potential but challenged by poor environmental hygiene and a lack of public facilities. The work programs included education on waste management using the 3R (Reduce, Reuse, Recycle) concept, distribution of trash bins, community clean-up activities, installation of street name signs, a coloring competition for children, and the construction of a low-smoke waste incinerator. An educational and participatory approach was employed to increase community awareness and involvement. The results showed improved public awareness regarding environmental cleanliness, better area organization through signage, and enhanced children's creativity through competitions. Students also gained valuable experience in community interaction, leadership, and implementing local solutions. This program was considered effective in promoting a cleaner, more organized, and empowered village through collaboration between students and residents.